Supporting self-regulated hypermedia learning through prompts - Bannert, Maria; Reimann, Peter (Instructional science, 2012)
The aim of this research was to develop and evaluate tools and supports for self-regulated learning with hypertext information structures, such as Web pages. Two kinds of supports for self-regulated learning were developed and tested experimentally: Prompting and Prompting with Training. In Experiment 1, Prompting was tested with a pre-post-test between subject design, including thinking-aloud data. Students of the experimental group (n = 20) were prompted for self-regulation activities that had to be followed while learning basic learning theory. No self-regulation support was offered in the control group (n = 20). In Experiment 2 (Prompting with Training), the experimental group (n = 20) received a short training, in addition to the prompting: the self-regulated learning activities were explained in detail, demonstrated and practiced right before the learning session. Again, no self-regulation support was offered in the control group (n = 20). Analyses of learning processes and learning outcomes confirm partly the positive effects of both measures of self-regulated learning prompts. The more extended measure (with training) had superior effects on students' learning transfer performance and acceptance. Implications for the design of instructional support to improve self-regulated learning with computer-based learning environments are discussed.